Bawaslu’s Oversight of Digital Campaign Dynamics on Social Media in the 2024 Tanah Datar Regional Head Election - Nurjannah, Zakiati; Caniago, Sulastri; Husni, Alfi; Emrizal (Al Ushuliy: Jurnal Mahasiswa Syariah dan Hukum, 2025)
This thesis examines the supervision carried out by the Election Supervisory Agency (Bawaslu) over digital campaign activities on social media during the 2024 Regional Head Election (Pilkada) in Tanah Datar. The study focuses on three main issues: the forms and characteristics of digital campaigns that emerged on social media platforms, the supervisory mechanisms employed by Bawaslu in responding to these dynamics, and the challenges faced by Bawaslu in exercising its oversight function amid the rapid development and openness of digital information. This research adopts a qualitative field research approach. Data were collected through in-depth interviews with relevant stakeholders, documentation analysis, and observation of local social media accounts that were active during the campaign period. The collected data were analyzed descriptively and qualitatively using several analytical frameworks, including surveillance theory, campaign theory, institutional theory of Bawaslu, and the perspective of fiqh siyasah tanfidziah. The findings indicate that digital campaigns in the 2024 Tanah Datar Pilkada were not limited to informational, persuasive, and mobilizational content, but also evolved into spaces of political criticism, satire, humor, and complex public interaction. This development confirms that social media has become a strategic arena for shaping public opinion, while simultaneously presenting significant challenges for electoral supervision. Bawaslu’s supervisory efforts—implemented through direct, indirect, and preventive mechanisms—reflect an institutional attempt to adapt to digital realities. However, their effectiveness remains constrained by technical limitations, the absence of detailed regulatory frameworks governing digital campaigns, and relatively low levels of public participation. This condition illustrates a gap between positive legal norms governing elections and the actual practices of digital campaigning in the field. From the perspective of fiqh siyasah tanfidziah, electoral supervision constitutes a mandate that must be carried out fairly and oriented toward the public interest (maslahah). Accordingly, this study emphasizes the importance of strengthening digital campaign regulations, enhancing supervisory technological capacity, and encouraging broader public involvement to ensure that digital campaign oversight is more effective, just, and aligned with both legal principles and sharia values.